(untitled) (Research, Society and Development, 2021)
The present research aimed to evaluate the physical properties of an LATOSSOLO VERMELHO Eutroférrico after the cultivation of maize second crop and cover crops grown in monoculture or intercropping. This research was developed in the area of ​​the Copagril cooperative in Marechal Cândido Rondon-PR. The experimental design was in randomized blocks consisting of six treatments: (T1) Maize monoculture (control), (T2) Maize intercropped with Brachiaria (Brachiaria ruzizienses), (T3) Brachiaria in monoculture, (T4) Crotalaria (Crotalaria spectabilis) in monoculture, (T5) Corn intercropped with Crotalaria, (T6) Black oat (Avena sativum) in monoculture. Up to 0.10 m the effect of corn, Brachiaria ruziziensis, Crotalária spectabilis and black oat crops were similar for soil density and porosity. While, at depth from 0.10 to 0.20 m, Brachiaria ruziziensis was more efficient in increasing macroporosity than Crotalaria spectabilis. The Crotalaria spectabilis cultivated in monoculture was not able to reduce soil resistance to penetration.